2004
DOI: 10.1080/08035250410023115
|View full text |Cite
|
Sign up to set email alerts
|

Mother-infant skin-to-skin contact after delivery results in early recognition of own mother's milk odour

Abstract: Our study provides evidence that mother-infant skin-to-skin contact for more than 50 min immediately after birth results in enhanced infant recognition of their own mother's milk odour and longer breastfeeding duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Seven studies with 324 mother/infant pairs reported data on the duration of breastfeeding in days. Six of the seven studies (De Chateau 1977; Mizuno 2004; Shiau 1997; Sosa 1976b; Sosa 1976c; Svejda 1980) found a longer duration of breastfeeding in the SSC dyads (mean difference (MD) 42.55 days, 95% CI −1.69 to 86.79). However, overall, the difference between groups did not reach statistical significance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies with 324 mother/infant pairs reported data on the duration of breastfeeding in days. Six of the seven studies (De Chateau 1977; Mizuno 2004; Shiau 1997; Sosa 1976b; Sosa 1976c; Svejda 1980) found a longer duration of breastfeeding in the SSC dyads (mean difference (MD) 42.55 days, 95% CI −1.69 to 86.79). However, overall, the difference between groups did not reach statistical significance.…”
Section: Resultsmentioning
confidence: 99%
“…Substantial differences were found between studies in the amount of separation that occurred in the control group. In eight studies (Chwo 1999; Hales 1977; Huang 2006; Mizuno 2004; Shiau 1997; Sosa 1976a; Sosa 1976b; Sosa 1976c), infants were removed from their mothers immediately postbirth and reunited 12 to 24 hours later. In five studies (Carlsson 1978; Craig 1982; Gouchon 2010; Svejda 1980; Thomson 1979), the mothers held their swaddled infants for about five minutes soon after birth and then were separated from their infants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human newborns are responsive to their environments by modifying the movements of their mouths: they alter their suckling patterns for sweet solutions [1], and they respond to the odor of their mother’s breast milk by making mouthing movements [2]. Newborns also use their mouths to interact with visual stimuli: Meltzoff and Moore [34] found that within minutes after birth, infants respond to facial gestures with matching facial gestures.…”
Section: Introductionmentioning
confidence: 99%